A case of lymphangioleiomyomatosis with diffuse large B-cell lymphoma: Usefulness of FDG-PET. (2020) - Orimo, Mami; Kondo, Mitsuko; Takeyama, Kiyoshi; Masui, Kenta; Tanaka, Junji; Tagaya, Etsuko
Abstract: Lymphangioleiomyomatosis (LAM) is characterized by cystic lung disease, abdominal tumor and involvement of the axial lymph nodes. We report a very rare case of LAM with malignant lymphoma. A 51-year-old female had medical history of recurrent pneumothorax and nephrectomy for a left renal angiomyolipoma and was diagnosed with LAM by video-assisted thoracoscopic surgery at the age of 30. She presented with left neck mass. Computed tomography and magnetic response imaging showed multiple enlarged cervical lymph nodes. 18 F-fluorodeoxyglucose-positron emission tomography (FDG-PET) showed abnormal uptake in the mass. We suspected a malignant tumor or extrapulmonary lesion of LAM, and performed surgical biopsy. Pathologically, diffuse large B-cell lymphoma was diagnosed, but LAM was not detected. After she received six cycles of R–CHOP chemotherapy, FDG-PET turned negative and complete metabolic response was achieved. As LAM is reported to be silent for FDG-PET, unusual uptake of FDG is useful for identifying other neoplasms. For this case, FDG-PET was useful for the differential diagnosis and therapeutic evaluation.